Citizenship culture and the problematic of building identity security - Adel, Boukhezani; Lakhdar, Chetoui (The International tax journal, 2026)
This article examines the dialectical relationship between citizenship culture and the problematic of building identity security in light of the profound transformations affecting the contemporary world, driven by globalization, the development of information and communication technologies, and the increasing cultural pluralism within the modern state. It is based on the central hypothesis that consolidating a citizenship culture grounded in rights, duties, participation, and equality constitutes a key approach to strengthening identity security and preserving national cohesion without falling into exclusion or fragmentation. The article highlights that citizenship is no longer merely a legal status of belonging, but has become a social, political, and cultural practice shaped through socialization institutions such as education, media, the state, and civil society. Likewise, national identity is no longer a fixed structure but a dynamic construction influenced by globalization and socio-economic transformations. It further argues that identity security is based on a balance between preserving cultural specificity, engaging with global influences, and managing diversity within society, while emphasizing the central role of the state in producing a unifying national narrative, consolidating social justice, and strengthening institutional trust.